Exogenous calcium: Its mechanisms and research advances involved in plant stress tolerance - Feng, Di; Wang, Xuejie; Gao, Junping; Zhang, Chenxi; Liu, Hao; Liu, Ping; Sun, Xiaoan (Frontiers in Plant Science, 2023)
Abiotic stresses are various environmental factors that inhibit a normal plant growth and limit the crop productivity. Plant scientists have been attempting for a long time to understand how plants respond to these stresses and find an effective and feasible solution in mitigating their adverse impacts. Exogenous calcium ion as an essential element for the plant growth, development and reproduction has proven to be effective in alleviating plant stresses through enhancing its resistance or tolerance against them. With a comprehensive review of most recent advances and the analysis by VOSviewer in the researches on this focus of “exogenous calcium” and “stress” for last decade, this paper summarizes the mechanisms of exogenous calcium that are involved in plant defensive responses to abiotic stresses and classifies them accordingly into six categories: I) stabilization of cell walls and membranes; II) regulation of Na+ and K+ ratios; III) regulation of hormone levels in plants; IV) maintenance of photosynthesis; V) regulation of plant respiratory metabolism and improvement of root activities; and VI) induction of gene expressions and protein transcriptions for the stress resistance. Also, the progress and advances from the updated researches on exogenous calcium to alleviate seven abiotic stresses such as drought, flooding, salinity, high temperature, low temperature, heavy metals, and acid rain are outlined. Finally, the future research perspectives in agricultural production are discussed.